التوجيهات النحوية للإمام النووي : دراسة تحليلية من خلال كتاب المجموع - Md Noor Bin Hussin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The Arabic language is closely related to Ilm Fiqhas they are inseparable from one another. Ilm Fiqh and all its aspects depend highly on the Arabic language, especially its grammar in order to determine Shariah Hukm. Thus, the study of Arabic grammar is not only for the sake of the Arabic language or not just mere knowledge on grammar, but also for other purposes, especially understanding Islamic knowledge. It is also considered the means to achieve certain goals in several knowledge disciplines. This research is generated due to lack of in-depth and focused studies in the areas of Nahw and Fiqh.The researcher examines the discussion on Arabic grammar in Kitab Majmu' by Imam Nawawi. This study aims to expose the functional grammar in Imam Nawawi's personality and his book as well as explores the dilalat of functional grammar found in the book. This study is based on descriptive and analytical methodologies. The study found that Ilm Nahw indeed helps in understanding Shariah texts. The study also found that Imam Nawawi is an expert in the field of Ilm Nahw which is shown through his discussion and debate on the issues of Arabic grammar on Fiqh.